2021
DOI: 10.3390/pharmaceutics13111793
|View full text |Cite
|
Sign up to set email alerts
|

Medical Applications of Metallic Bismuth Nanoparticles

Abstract: Recent reviews described the efficient syntheses of metallic bismuth nanoparticles. Nevertheless, few studies have been published on the medical applications of these nanoparticles compared to the number of studies on the well-documented clinical use of the bismuth(III) complex. An analysis of the literature revealed the significant potential of metallic bismuth nanoparticles in different theranostic applications. In the diagnostic field, preclinical proofs of concept have been demonstrated for X-ray, photoaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…In the vast majority of the studies, spherical silver nanoparticles were used, obtained from different extracts, having various sizes: A. priceps , 5–30 nm [ 125 ]; S. xanthocarpum , 4–18 nm [ 32 , 126 ]; T. vernicifluum , 4–20 nm [ 127 ]; C. longa [ 128 ] and A. nilotica , 22–66 nm [ 124 ]; P. putida , 6–16 nm [ 35 ]; A. calamus , 5–60 nm [ 129 ]; A. nilotica , 22–55 nm [ 130 ]. The most common effect on the bacterial colonies was inhibition of growth, which was presented in six of the papers [ 124 , 125 , 127 , 128 , 131 , 132 , 133 , 134 ], followed by activation of reactive oxygen species production [ 130 , 132 ], inactivation of H. pylori urease [ 131 , 135 ], bacterial DNA fragmentation and consecutive loss of viability [ 130 ], damage to the bacterial cellular membrane [ 132 ], and activation of antioxidant activity [ 136 ].…”
Section: The Antibacterial Mechanism Of Silver Nanoparticles: An Exte...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the vast majority of the studies, spherical silver nanoparticles were used, obtained from different extracts, having various sizes: A. priceps , 5–30 nm [ 125 ]; S. xanthocarpum , 4–18 nm [ 32 , 126 ]; T. vernicifluum , 4–20 nm [ 127 ]; C. longa [ 128 ] and A. nilotica , 22–66 nm [ 124 ]; P. putida , 6–16 nm [ 35 ]; A. calamus , 5–60 nm [ 129 ]; A. nilotica , 22–55 nm [ 130 ]. The most common effect on the bacterial colonies was inhibition of growth, which was presented in six of the papers [ 124 , 125 , 127 , 128 , 131 , 132 , 133 , 134 ], followed by activation of reactive oxygen species production [ 130 , 132 ], inactivation of H. pylori urease [ 131 , 135 ], bacterial DNA fragmentation and consecutive loss of viability [ 130 ], damage to the bacterial cellular membrane [ 132 ], and activation of antioxidant activity [ 136 ].…”
Section: The Antibacterial Mechanism Of Silver Nanoparticles: An Exte...mentioning
confidence: 99%
“…Since the early 19th century, they have been used to treat digestive complaints; nonetheless, their antibacterial action remains poorly known, and no cases of bismuth resistance have been reported [ 97 , 140 , 141 ]. An extended analysis of 41 studies by Catherine Gomez et al showed an important antibacterial effect of bismuth-based nanoparticles [ 135 ]. Griffith et al provided important information regarding the unique effect of bismuth against H. pylori infection [ 142 ].…”
Section: Other Metal-based Nanoparticles Used In the Treatment Of ...mentioning
confidence: 99%
“…However, the major limitations of nanoparticulates are toxicological aspects of reactive nanoparticles and researchers need more attention to detailed demonstration to explore these nanoparticles at the next level [13]. Bismuth (Bi) is a diamagnetic semimetal with nominal bandgap, and also, this material exhibits attractive properties like thermal conductivity, magnetoresistance, and dominant anisotropic electronic features; these potential characteristics of bismuth nanoparticles trigger and tune the electronic properties, which may influence the sensitization enhancement ratio (SER) towards the development of cancer treatment [14].…”
Section: Properties Of Bismuth Nanoparticulatesmentioning
confidence: 99%
“…Bismuth-based materials, owing to the high affinity of bismuth towards sulfur, nitrogen and oxygen, have been constructed into diverse forms ( e.g. , complexes, oxyhalides and composite oxides) via various approaches such as conventional, hydrothermal, sonochemical and microwave-assisted methods [ 15 , [23] , [24] , [25] , [26] , [27] ]. Remarkably, metal-organic frameworks (MOFs), a group of hybrid crystalline materials composed of metal ions and organic ligands, demonstrate high surface area and ultrahigh porosity [ [28] , [29] , [30] , [31] , [32] , [33] , [34] ].…”
Section: Introductionmentioning
confidence: 99%